2007
DOI: 10.1103/physrevb.76.245436
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline surface phases of the liquid Au-Si eutectic alloy

Abstract: A two dimensional crystalline layer is found at the surface of the liquid eutectic Au82Si18 alloy above its melting point TM = 359 • C. Underlying this crystalline layer we find a layered structure, 6-7 atomic layers thick. This surface layer undergoes a first-order solid-solid phase transition occurring at 371 • C. The crystalline phase observed for T>371 • C is stable up to at least 430 • C. Grazing Incidence X-ray Diffraction data at T>371 • C imply lateral order comprising two coexisting phases of differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 85 publications
3
44
0
Order By: Relevance
“…Si) and crystal structures. [2][3][4][5][6] More recently, a stable two-dimensional (2D) gold silicide has been evidenced following surface crystallisation of the eutectic Au 82 Si 18 liquid above the eutectic temperature T E ¼ 359 C. 7 It was shown to have an Au 4 Si 8 composition and a rectangular crystal structure, stable up to 371 C. 8 This 2D crystalline silicide phase has also been obtained under ultra high vacuum (UHV) conditions following deposition of a 3 nm Au layer on a Si(100) substrate and subsequent annealing above the eutectic temperature (T E ). 9 Other Au/Si alloys were also obtained in UHV conditions either at room temperature (RT) [10][11][12] or by annealing thicker Au films (10-100 nm) deposited on a Si substrate.…”
mentioning
confidence: 99%
“…Si) and crystal structures. [2][3][4][5][6] More recently, a stable two-dimensional (2D) gold silicide has been evidenced following surface crystallisation of the eutectic Au 82 Si 18 liquid above the eutectic temperature T E ¼ 359 C. 7 It was shown to have an Au 4 Si 8 composition and a rectangular crystal structure, stable up to 371 C. 8 This 2D crystalline silicide phase has also been obtained under ultra high vacuum (UHV) conditions following deposition of a 3 nm Au layer on a Si(100) substrate and subsequent annealing above the eutectic temperature (T E ). 9 Other Au/Si alloys were also obtained in UHV conditions either at room temperature (RT) [10][11][12] or by annealing thicker Au films (10-100 nm) deposited on a Si substrate.…”
mentioning
confidence: 99%
“…10 However, none of the experimental studies mentioned above provided detailed structure information about the observed alloy phases due to the complexity of Au-Si alloys. 10,17,[20][21][22] Resolving the structures of complex alloys experimentally is still very difficult, which impedes the understanding and further optimization of the alloys for applications. 23 On the other hand, computational algorithms and methods for ab initio structure prediction can speed up the investigation of the structures of Au-Si alloy.…”
Section: Introductionmentioning
confidence: 99%
“…10,21 Another study reported that a spherical bulk-like crystal structure, which is the first Si-rich Au-Si alloy with 33.3% of the Au content, can be observed after annealing. 42 In our present study, we found that the energy of the structure at 33.3% Au (i.e., Au 2 Si 4 ) from our GA search is located in a deep minimum in the convex hull (Fig.…”
mentioning
confidence: 99%
“…Meanwhile, another method of fabrication for the synthesis of SiNWs has been studied; this procedure involves a bottom-up approach using chemical vapor deposition (CVD). Normally, in the bottom-up synthesis of SiNWs, Au is used as a catalyst because it has an Au/Si eutectic point at 363 C, but the melting points of Si and Au are over 1000 C. 6 Under suitable synthesis conditions, Si atoms decomposed from siliconcontaining gas are di®used through the catalyst and grow vertically. 7,8 However, the detachment of the synthesized SiNWs from the substrate and their rearrangement to match the electrode gap precisely for the fabrication of electric devices, remains challenging.…”
Section: Introductionmentioning
confidence: 99%